Processing of discharge summaries in general practice: a retrospective record review - Spencer, Rachel; Spencer, Simon E.F.; Rodgers, Sarah; Campbell, Stephen; Avery, Anthony (Royal College of General Practitioners, 2018)
Background: There is a need for greater understanding of the epidemiology of primary care patient safety in order to generate solutions to prevent future harm. Aim: To estimate the rate of failures in processing actions requested in hospital discharge summaries and to determine factors associated with these failures. Design and setting: We undertook a retrospective records review. Our study population was emergency admissions for patients aged ≥75 years, drawn from ten practices in three areas of England. Method: One GP researcher reviewed the records for 300 patients after hospital discharge to determine the rate of compliance with actions requested in the discharge summary and to estimate the rate of associated harm from non-compliance. Where GPs documented decision making contrary to what was requested, these instances did not constitute failures. Data were also collected on time taken to process discharge communications. Results: There were failures in processing actions requested in 46% (112/246) of discharge summaries (CI 39-52%). Medications changes were not made in 17% (124/750) of requests (CI 14-19%). Tests were not completed for 25% of requests (CI 16-34%) and 27% of requested follow-ups were not arranged (CI 20-33%). The harm rate associated with these failures was 8%. Increased risk of failure to process test requests was significantly associated with the type of clinical IT system and male patients. Conclusion: Failures occurred in the processing of requested actions in almost half of all discharge summaries, and with all types of action requested. Associated harms were uncommon and most were of moderate severity.